Pengaruh Profitabilitas, Likuiditas, Pertumbuhan Perusahaan, dan Ukuran Perusahaan terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Fini Rahma; Retno Fuji Oktaviani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research aims to determine the influence of Profitability, Liquidity, Company Growth, and Company Size on Company Value in Manufacturing Companies in the Food and Beverage Sub Sector on the Indonesian Stock Exchange in 2019-2023. This research uses quantitative methods with a population and sample from Food and Beverage Sub-Sector Manufacturing Companies on the Indonesian Stock Exchange for 2019-2023. 24 companies were the object of this research which were determined using certain criteria. The analytical methods in this research consist of the classic assumption test, correlation coefficient analysis test, multiple linear regression analysis test, determination analysis test (R2), t-test, and F test. Meanwhile, the data analysis method used is multiple linear regression with a significance value 0.05 using Static Product and Service Solution (SPSS) Version 29.0. The results of this research show that partial profitability and liquidity affect company value, while company growth and company size do not affect company value. Simultaneously profitability, liquidity, company growth, and company size influence company value.